Ocena funkcjonalna osób trenujących boks z wykorzystaniem testu Functional Movement Screen (FMS) = Functional evaluation of competitors practicing boxing using the Functional Movement Screen (FMS) - Bartosz Kochański; Anna Kałużna; Krystian Kałużny; Łukasz Wołowiec; Jacek Leoniuk; Magdalena Hagner-Derengowska; Walery Zukow; Wojciech Hagner (Kazimierz Wielki University, 2015)
Kochański Bartosz, Kałużna Anna, Kałużny Krystian, Wołowiec Łukasz, Leoniuk Jacek, Hagner-Derengowska Magdalena, Zukow Walery, Hagner Wojciech. Ocena funkcjonalna osób trenujących boks z wykorzystaniem testu Functional Movement Screen (FMS) = Functional evaluation of competitors practicing boxing using the Functional Movement Screen (FMS). Journal of Education, Health and Sport. 2015;5(10):19-28. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.31841 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A19-28 https://pbn.nauka.gov.pl/works/644919 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015.   Ocena funkcjonalna osób trenujących boks z wykorzystaniem testu Functional Movement Screen (FMS) Functional evaluation of competitors practicing boxing using the Functional Movement Screen (FMS)   Bartosz Kochański1, Anna Kałużna1, Krystian Kałużny1, Łukasz Wołowiec2, Jacek Leoniuk3, Magdalena Hagner-Derengowska3,4, Walery Zukow5, Wojciech Hagner1   1Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; 2II Katedra Kardiologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; 3Bydgoska Szkoła Wyższa w Bydgoszczy; 4Katedra Neuropsychologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; 5Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy;   Streszczenie   Wstęp. Boks ze względu na swoją specyfikę związany jest z dużym ryzykiem występowania urazów i kontuzji. Istotnym elementem profilaktyki pierwotnej jest kompleksowa funkcjonalna ocena fizjoterapeutyczna. Pozwala ona na wczesne wykrycie nieprawidłowości motorycznych, określenie predyspozycji do urazu oraz wprowadzenie odpowiednich technik korekcyjnych. Jednym z narzędzi służących do kompleksowej oceny funkcjonalnej sportowca jest  Functional Movement Screen (FMS). Cel pracy. Celem pracy jest ocena funkcjonalna osób trenujących boks z wykorzystaniem testu Functional Movement Screen (FMS). Materiał i metody. Badania przeprowadzono na grupie 25 osób trenujących zawodowo boks (w tym 20 mężczyzn (80%) oraz 5 kobiet (20%)) w klubie sportowym WKB "Start" Włocławek. Ocenę funkcjonalną wykonano z wykorzystaniem testu Functional Movement Screen (FMS). Badania zostały przeprowadzone z wykorzystaniem urządzenia oraz protokołu do testu FMS. Wyniki. U zawodników zaobserwowano nieprawidłowości w podstawowych wzorcach ruchowych, zwłaszcza w mobilności. Średni wynik w teście FMS uzyskany przez zawodników uprawiających boks to 14,84/21 punktów. 28% badanych uzyskało wynik poniżej 14 punktów, co zwiększa ryzyko pojawienia się urazu z 15% do 51%. U badanych zaobserwowano szereg asymetrii (u 40% w teście "Mobilność obręczy barkowej" oraz u 40% w teście ASLR). Wnioski 1. U osób trenujących boks obserwuje się nieprawidłowości w podstawowych wzorcach ruchowych w teście FMS. 2. Ryzyko wystąpienia urazu u osób trenujących boks wg skali FMS jest stosunkowo duże. 3. U  osób trenujących boks obserwuje się szereg asymetrii i deficytów w teście FMS.   Abstract   Introduction. The specificity of boxing is associated with a high risk of injuries and injury. An important element of primary prevention is the comprehensive functional assessment of the athlete. It allows for early detection of abnormalities in motor, determining predisposition to injury and introducing appropriate corrective techniques. One of the tools for comprehensive functional assessment of the athlete is a Functional Movement Screen (FMS). Aim of the study. The aim of the study was to evaluate the functional test boxers using Functional Movement Screen (FMS). Materials and methods. The study was conducted on a group of 25 people practicing boxing professionally (including 20 men (80%) and 5 women (20%)) in the WKB "Start" Włocławek. Functional evaluation was performed by using the test Functional Movement Screen (FMS). The study was conducted using the device and the test protocol to the FMS. Results. Abnormalities were observed in the basic movement patterns, in particular in mobility. The average score in the test FMS earned by players practicing boxing is 14.84/21 points. 28% of patients reached a score below 14 points, which increases the risk of injury from 15% to 51%. In boxers also observed asymmetry (40% in the test "Shoulder Mobility" and 40% ASLR test). Conclusions. 1. In the boxers observed irregularities in the basic movement patterns in the test FMS. 2. Risk of injury the boxers according to the scale of FMS is relatively large. 3. For people practicing boxing observed asymmetries and deficits in the test FMS.   Słowa kluczowe: ocena funkcjonalna, FMS, Functional Movement Screen, boks. Keywords: functional evaluation, FMS, Functional Movement Screen, boxing.